MARCADOR INFLAMATÓRIO COMO MEDIADOR ENTRE ADIPOSIDADE E SONO EM ADULTOS DA COORTE DE 1993 DE PELOTAS - SILVA, Emanuellen Coelho da (2026)
Introduction: Evidence shows that body adiposity is associated with changes in sleep, and inflammatory processes may play a mediating role in this relationship. Objective: To evaluate whether C-reactive protein (CRP) at 22 years mediates the association between the Index of Fat Mass (IFM) at 18 years and sleep duration at 30 years in adults from the 1993 Pelotas Birth Cohort. Methods: This longitudinal study included 2,158 participants. IFM was assessed at 18 years using air-displacement plethysmography (Bod Pod®). Serum CRP was measured at 22 years, and mean sleep duration (hours) was estimated at 30 years using accelerometry. Mediation analyses were conducted using the mediation package in R (version 2025.06.1+524), considering crude and adjusted models for sex, skin color, education, employment, alcohol consumption, smoking, screen time, food intake, physical activity, illicit drug use, anxiety, and depressive symptoms. The robustness of the findings was tested through a sensitivity analysis. Results: In the crude analysis, IFM was positively associated with sleep duration (β: 0,016; 95% CI: 0,004; 0,027; p = 0,007). In the adjusted analysis, this association persisted but became negative (β: −0,020; 95% CI: −0,034; −0,006; p = 0,003). In the unadjusted mediation analysis, CRP mediated the association between IFM and sleep (ACME = 0,007; p = 0,004), although the average direct effect (ADE) was not significant. After adjusting for covariates, CRP mediation lost significance (ACME = 0,001; p = 0,374), and the direct effect of IFM became negative and significant (ADE = −0,022; p = 0,004). Sensitivity analysis indicated that the mediating effect was small and not robust to unmeasured confounders. Conclusion: The findings suggest that CRP does not play a relevant mediating role in the association between early adiposity and sleep duration in adulthood. Conversely, higher IFM levels in youth were directly associated with shorter sleep duration at age 30, emphasizing the importance of preventing excess adiposity from early adulthood.